Community participation in the electricity network development project in Bekasi from ecological citizenship perspective - Faizal, Muhammad; Rusnaini, Rusnaini; Gunawati, Dewi (Indonesian Journal of Multidisciplinary Science, 2024)
This research explores the role of community participation in the electricity network construction project in Bekasi Regency, by viewing it through the lens of ecological citizenship. Ecological citizenship provides a framework for understanding the link between community participation and ecological responsibility in the context of energy infrastructure development. This research adopts a qualitative approach with a focus on in-depth understanding of the dynamics of community participation, influencing factors, and its impact on environmental sustainability. It is hoped that the research results will provide in-depth insight into the extent to which community participation can increase the sustainability of electricity network development projects. In addition, this research also aims to identify factors that influence community ecological participation in the project. Policy implications and recommendations will be generated to guide the development of similar infrastructure projects in the future by considering the ecological citizenship perspective.